Compiling invest-oriented integrated reporting: advantages, standards, recommendations - Momot, Tetiana; Karpushenko, Maria; Sobolieva, Hanna; Lytovchenko, Olena; Filatova, Iryna (Eastern-European Journal of Enterprise Technologies, 2021)
Meeting the information needs of investors interested in acquiring a share of the enterprise, or individual intangible assets, the rights to use them, has led to the search for new concepts and models for compiling reporting information. It is important to know how the technologies used by an enterprise affect the environmental condition, what costs are necessary for personnel training, for staying competitive, etc. Under such conditions, the classic model of financial reporting does not meet modern requirements – it is retrospective in nature. To persuade investors to invest in companies focused on creating value, it is important to compile investment-oriented corporate reporting. This paper reports the devised theoretical and methodological provisions, as well as the substantiation of practical recommendations for compiling investment-oriented integrated reporting, which includes a sequence of activities and a system of indicators for assessing the financial and non-financial components of business operations, including indicators of the environmental and social activities of an enterprise, which ensures the transparency of information in terms of business risks and their management. It is stated that the main goal of investment-oriented corporate reporting is to inform users about increasing the company's market value. Indeed, the reflection of the importance of social and environmental priorities, attention paid and efforts applied made to resolve social issues give confidence in the reliability of business and stimulate the attraction of investment resources. The examples of the companies chosen for this study have proven that the submission of complete information based on the groups of non-financial indicators of integrated reporting is a factor in increasing the market value of the company, and, accordingly, enhancing its investment attractiveness. The devised proposals make it possible to summarize in a single format information about the activities of an enterprise, related risks, and its investment potential